Use of Bilberry and Blackcurrant Pomace Powders as Functional Ingredients in Cookies - Violeta Nour; Ana Maria Blejan; Georgiana Gabriela Codină (Applied Sciences)
The purpose of the present study was to evaluate the effects of partially replacing wheat flour with bilberry (BIPP) and blackcurrant (BCPP) pomace powders at 2.5%, 5%, and 10% levels on dough texture and rheology and on the proximate composition, color, titratable acidity, pH, spread ratio, total phenolic content, DPPH radical scavenging activity, and textural and sensory properties of cookies. BIPP showed higher protein, fiber, and water absorption capacity while also showing lower fat and titratable acidity as compared with BCPP. The incorporation of BIPP and BCPP in cookies resulted in lower protein and higher fat, fiber, and mineral contents. Dough hardness, consistency, and stiffness increased while the hardness, cohesiveness, and chewiness of the cookies were found to decrease with the increase in pomace levels. A seven-fold increase in the total phenolic content of the cookies was recorded at a 10% replacement level of wheat flour with BIPP, reaching 214.73 mg GAE/100 g, while only a three-fold increase was found for 10% BCPP (90.18 mg GAE/100 g). The enrichment with BIPP and BCPP improved the sensory properties, with the 10% addition level presenting the highest acceptance. The results indicate that bilberry and blackcurrant pomace could be utilized as a sustainable source of fiber and bioactive compounds for adding nutritional, technological, and sensory benefits to the cookies.